2005
DOI: 10.1007/s00535-005-1655-3
|View full text |Cite
|
Sign up to set email alerts
|

A study of arteriosclerosis in healthy subjects with HBV and HCV infection

Abstract: Infection with HBV or HCV does not influence the severity of arteriosclerosis in healthy subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 32 publications
2
31
0
4
Order By: Relevance
“…22 In Japanese subjects, infection with HBV or HCV did not influence the severity of arteriosclerosis. 23 Moreover, chronic HBV and HCV infections were not associated with the presence or severity of coronary artery disease. 24 On the other hand, Ishizaka et al 25 reported that HCV seropositivity was independently associated with carotid arterial plaque and carotid intima-media thickening in 4784 individuals who underwent a general health screening test.…”
Section: Discussionmentioning
confidence: 97%
“…22 In Japanese subjects, infection with HBV or HCV did not influence the severity of arteriosclerosis. 23 Moreover, chronic HBV and HCV infections were not associated with the presence or severity of coronary artery disease. 24 On the other hand, Ishizaka et al 25 reported that HCV seropositivity was independently associated with carotid arterial plaque and carotid intima-media thickening in 4784 individuals who underwent a general health screening test.…”
Section: Discussionmentioning
confidence: 97%
“…[14] In a healthy population, Moritani et al also showed that presence of HBV and HCV infection had not affected the severity of arteriosclerosis. [15] In our study, age-, sex-, and dialysis duration-matched non-diabetic HCV(+) and HCV(−) HD patients were compared. There was no difference between groups with respect to smoking habits, hypertension, left ventricular hypertrophy, and family history of diabetes or hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…The authors then read the full text of all 29 articles, and excluded studies that were not suitable for this meta-analysis. Eleven articles were excluded because they were the incorrect type of articles, such as reviews and workshop summaries; five articles had the wrong methodology (three included patients who had concurrent infection with other pathogens); one article was a cross-sectional study and did not study the relationship between exposure to HBV and atherosclerosis [15]; one article that considered cerebrovascular disease as an outcome included both ischaemic and haemorrhagic cerebrovascular disease [7]; seven articles had the wrong outcomes (they studied the parameters related to atherosclerosis but did not set a threshold to define atherosclerosis) [4][5][6][16][17][18][19]; and one article was a cohort study, but there was no other cohort study to perform the meta-analysis [11]. Finally, we included five eligible studies for the meta-analysis [8-10, 12, 13].…”
Section: Study Identification and Selectionmentioning
confidence: 99%